029 Importance of face-to-face consultation in complex decision-making. Issue 12 (14th November 2019) - Nicholas, Richard; Solari, Alessandra; Wilkie, David
Abstract : Recent focus on self-care and telemedicine have challenged the role of face-to-face consultations in medicine. Disease activity, national guidelines, life goals e.g. pregnancy, multiple therapies and varying side effects need to be considered on starting disease modifying treatments in multiple sclerosis (MS). We studied the factors driving decisional conflict (DC), a measure of a decision satisfaction in people with (pw)MS making this decision. Methods: Antecedents, features and outcomes of the consultation were measured in pwMS attending clinics who were making decisions about treatment. The SURE scale for DC was the primary outcome. Results: The patient activation measure (PAM) was the only antecedent prior to the consultation associated with DC (n=72, Adjusted R2 0.062, p=0.020). In the consultation shared decision making (SDM) (p=0.000) and PAM (0.043) were both drivers of DC (n=67, Adjusted R2 0.383, p=0.000). In turn the significant factor associated with the SDM score from within the consultation was satisfaction with the health care professional (HCP) (n=68, Adjusted R2 0.220, p=0.000). Conclusions: Patient engagement impacts DC but the HCP delivering the optimal shared decision-making approach is also significant in reducing DC. In complex decisions there is a clear role for the face-to-face consultation in current practice.